Impact of social support on psychosocial symptoms and quality of life in cancer patients: results of a multilevel model approach from a longitudinal multicenter study - Sauer, Christina; Weis, Joachim; Faller, Hermann; Junne, Florian; Honig, Klaus; Bergelt, Corinna; Hornemann, Beate; Stein, Barbara; Teufel, Martin; Goerling, Ute; Erim, Yesim; Geiser, Franziska; et al. (Acta Oncologica, 2019)
Background: This prospective multicenter study aimed to investigate the courses of positive support (PS) and detrimental interaction (DI), two different aspects of social support, and the relation between social support and psychosocial distress and/or health-related quality of life (HRQOL) in a large sample of patients with different cancers. Methods: For this observational study, we enrolled adult patients with cancer from 13 comprehensive cancer centers (CCCs) in Germany. We included a total of 1087 patients in our analysis. We assessed the outcomes via standardized self-report questionnaires at three measurement points: at admission for acute care (T1), 6 (T2) and 12 months (T3) thereafter. Our outcome variables included PS and DI, depression and anxiety symptoms, distress, mental quality of life (MQoL) and physical QoL (PQoL). Data were analyzed using three-level hierarchical linear modeling (HLM) and group-based trajectory modeling. Results: During the first year after the cancer diagnosis, both PS and DI decreased in our sample. Baseline depression symptom severity was a significant predictor of PS and DI. Further analyses revealed significant associations between PS, DI and the course of depression and anxiety symptoms, and MQoL. PS buffered the negative effects of DI with regards to these variables. Low DI was associated with better PQoL, whereas PS was not. In general, the impact of social support on psychosocial outcomes was weak to moderate. Conclusions: Our findings provide evidence for the influence of PS and DI on psychosocial symptoms and HRQOL, and emphasize the importance of psycho-oncological interventions that strengthen PS and prevent or reduce DI for patients with cancer and their relatives.
CRIS-Team WoS Importer:2019-08-13